An ethnographic approach to the thematic classification of Christo-Kegites' Songs in Nigeria (2016)
This paper focuses on the songs of the Kegites’ Club, a socio-cultural group at university and polytechnic campuses in Nigeria with the aim of identifying their themes alongside the Christian songs from which they are derived. The analysis of the songs is based on Dell Hymes’ Ethnographic Framework, which identifies contextual variables that account for the various factors that are involved in different communicative events. Thirty songs, comprising 11 English versions and 19 Yorùbá versions are purposively selected for analysis in this study. Even though these songs are derived from the choruses sung by Christians in their fellowships and retain the lyrics of the choruses, they have been cleverly manipulated to underscore their own themes and identity as opposed to the themes of the Christian songs that serve as their sources